Investment decisions and capital accumulation: firm-level evidence from Brazil - Camêlo, Felipe Diogo (2018)
Using firm-level data from an administrative Brazilian dataset, I document a few stylized facts regarding capital stock accumulation patterns and investment decisions. Finding evidence largely in favor of micro-level lumpiness of investment as it was found for American firms, I document that there are a few particularities in the behavior of Brazilian firms. First, I document that the distribution of the growth rate of capital is more dispersed, with “fatter” tails. Second, I also show that, as economic activity, the volume of investment and capital stock are more concentrated on a small number of firms, micro-level lumpiness might have a bigger role in understanding aggregate movements. Third, I show that the observable characteristics of Brazilian firms explain a lot more of sudden movements in capital growth when compared to the U.S., after controlling for industry specific characteristics and other variables. Fourth and last, I compute statistical measures related to the investment rate distribution, which show that investment at the firm-level seems to be even “lumpier” in Brazil, with firms investing less on average, while experiencing more episodes of investment spikes and periods of inaction.